Nomenclature of real patients in health professional education by role and engagement: a narrative literature review (Canadian Medical Education Journal, 2022)
Research problem: Real patients living with a disease and engaged in the education of healthcare professionals are referred to by different terms. To address this, A.Towle proposed a draft taxonomy.Objective: Our objective is to extract from the literature the definitions given for the following terms: (1) patient educator, (2) patient instructor, (3) patient mentor, (4) partner patient, (5) patient teacher, (6) Volunteer Patient in order to clearly identify their roles and level of engagement.Methods: The literature search was carried out in Medline, CINAHL, PsychInfo and Eric by adding medical education or healthcare professional to our previously identified keywords to ensure that it is indeed literature dealing with real patients’ involvement in the education of healthcare professionals. Results: Certain terms refer to real and simulated patients. Roles are more or less well described but may refer to multiple terms. The notion of engagement is discussed, but not specifically. Conclusion: Explicitly defining the terms used according to the task descriptions and level of engagement would help contribute to Towle’s taxonomy. Real patients would thus feel more legitimately involved in health professional education.